Analisis Yuridis Problematika Pengakuan Masyarakat Hukum Adat Laman Kinipan - Ika Putri Rahayu; Apriska Widiangela; Lailatul Komaria (CV Rewang Rencang, 2021)
The conflict between the Indigenous Law Community (ILC) of Laman Kinipan with PT Sawit Mandiri Lestari (SML) regarding Kinipan customary forest clearing into oil palm plantations is still prolonged to this day. The recognition of customary law communities is also still a matter of debate due to the unclear and overlapping national legal systems. It leads to low legal protection for indigenous people, which is likely to injure indigenous peoples' constitutional rights as Indonesian citizens, one of which is the conflict that befell the ILC of Laman Kinipan. The government's action in the conflict case between the ILC of Laman Kinipan and PT SML was deemed not oriented in terms of good governance and violated the human rights of MHA Laman Kinipan.